ANALISIS SEMIOTIK PADA PUISI “KARANGAN BUNGA” KARYA TAUFIK ISMAIL - Fitria Dwi Widiastuti (Universitas 45 Surabaya, 2022)
Poetry is a literature that contains many building elements, one of which is the meaning of poetry, to analyze the meaning of a poem, a semiotic approach to poetry can be used. Semiotics has a meaning as a sign. The sign here can be a theme, value or meaning of a word or sentence in poetry. In this study, the researcher will analyze the poem entitled “Wreath of Flowers” ​​by Taufik Islamil using a semiotic approach, which is to tell the results of poetry analysis based on the data obtained. The research is based on the curiosity to know the meaning or value of the poem